Comparison of physicochemical and volatile flavor properties of neon flying squid (Ommastrephes bartramii), jumbo squid (Dosidicus gigas), and Argentine shortfin squid (Illex argentinus) during chilled storage - Huo, Jiancong; Yao, Hui; Li, Jiagen; Wang, Jinmei; Benjakul, Soottawat; Zhang, Bin (Frontiers in Nutrition, 2023)
The difference and similarities in the physicochemical and volatile flavor properties were determined in neon flying squid (OB), jumbo squid (DG), and Argentine squid (IA) mantles during 8 d of chilled storage. Physicochemical analysis indicated the chilled conditions induced rapid increases in pH value, total volatile basic nitrogen (TVBN), and carbonyl and malondialdehyde (MDA) content. In addition, myofibrillar protein (MP) content decreased and springiness in the OB, DG, and IA mantle samples declined with the extension of storage time. Importantly, OB mantles presented less chemical stability than the other two squid samples during 8 d of chilled storage. In addition, histological observations suggest DG mantle tissues presented more compact structures than those of the other two samples. Volatile flavor analysis showed propionaldehyde, 3-pentanone, trimethylamine, 3-furanmethanol, 2-methyl butyric acid, and 2-butanone were highly abundant in the squid mantles after storage, likely resulting from decomposition, oxidation, and degradation of proteins and lipids in the squid mantle, which varied with different squid species. The findings provide insight into the performance of three squid species during chilled storage.